(Not so) Clean Peak Energy Standards. (15th June 2021) - Shrader, Jeffrey G.; Lewis, Christy; McCormick, Gavin; Rabideau, Isabelle; Unel, Burcin
Abstract: The emissions impact of operating an energy storage system depends on the system's efficiency and the generation mix of the grid. Growth in energy storage, therefore, has the potential to increase emissions. Concerns about this outcome are currently prompting many policies to address the issue. We study a particularly popular policy proposal called the "Clean Peak Standard" that incentivizes storage to discharge during periods of high electricity demand. The stated goal of the policy is to shift storage discharge so that it offsets production from peak generators with high emissions. We show that the policy is largely ineffective at achieving this emissions reduction goal. The policy reinforces existing incentives faced by storage operators, so it does not have a strong effect on discharging behavior. It is also unable to capture high-frequency changes in marginal operating emissions rates. Alternative policies, such as a carbon tax, are more effective at reducing the emissions increase caused by storage operations. Policymakers considering Clean Peak-style policies should instead consider these alternative policies. Highlights: "Clean Peak Standards" are a new policy intended to reduce carbon emissions caused by grid storage. The policy pays storage operators to discharge electricity when demand is high. In our setting, storage causes 0.5 tons of emissions for each MWh of capacity. Clean Peak only reduces storage-related emissions by 5%. Even a $1 carbon tax would be more effective.